HAMBATAN-HAMBATAN DALAM MENGEMBANGKAN KECERDASAN LOGICAL/MATHEMATICAL PADA PEMBELAJARAN TERPADU MODEL WEBBED BERBASIS KECERDASAN JAMAK DI TKIT SALMAN AL FARISI II YOGYAKARTA(Studi Eksplorasi) - Caturiyati, Caturiyati; Hidayati, Kana; Lestari, Himmawati Puji (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2007)
One of the important intelligent component for children’s future and need to be developing early is logical/mathematical intelligent. Integrated learning is carried out in learning process that integrates sistematically and holistically the effort of developing child. One of the integrated learning model is webbed model, a learning model that integrates learning and developing for children in a topic that covers some subjects. TKIT Salman Al Farisi II applies learning with themes where those themes become a learning guide in class. It needs to investigate the constraints in optimizing of developing child’s logical/mathematical intelligent by integrated learning in TKIT Salman Al Farisi II. The results of this exploration research indicates that there are some constraints in developing child’s logical/mathematical intelligent. They are limited class room, limited facility, i.e. computer, children’s mood varying according to healthy and environment condition and different children’s ability.Key words : constraint, logical/mathematical intelligent, webbed model.